Developing a standardized and web-based data collection protocol in support to enhancing project monitoring and evaluation of the Bureau of Agricultural Research - Lales, Joell H. (University of the Philippines Diliman, 2011)
The Bureau of Agricultural Research (BAR) is one of the staff bureaus of the Department of Agriculture (DA) mandated to act as the central coordinating agency for R&D of the entire National R&D System for Agriculture and Fisheries (NaRDSAF). As such, BAR as the focal agency of the DA assigned to harmonize R&D as one of the core functions of the DA is continually beset with the challenge of strategically positioning interventions and investments to where it will create the most impact and value in terms of fueling the engine of growth and sustaining program gains. All government agencies are being gauged in terms of performance governed by a certain framework. The most recent framework in use by all government offices is the Organizational Performance Indicator Framework (OPIF) which was jointly developed by the NEDA and DBM to objectively assess the performance of a particular agency both physical and financial with respect to its accomplishments defined as its Major Final Outputs (MFO). This framework requires that business processes within the organization are systematized and continually improved as for some time, BAR had to struggle with processing and consolidating all its data specifically for all projects funded (new, on-going, terminated) for the basic fact that the stock-taking process did not follow a standardized modality. In view of the foregoing premises, this project then was conceptualized as an expansion of a previous practicum done by the author for DA-BAR aimed to develop an initial set of standardized parameters envisioned to improving monitoring and evaluation of the DA-BAR focusing on one of its flagship programs, the Community-based Participatory Action Research (CPAR). Specifically, the project aims : 1) to standardize parameters for data collection in support to enhancing the monitoring and evaluation protocol specific for CPAR; and 2) to systematize and ensure the relevance and accuracy of data collected through online and real time interaction/feedback mechanism among the protocol system administrators and its users e.g. BAR regional coordinators, Regional Research Manager, CPAR regional focal person. The methodology adopted for this project followed a two-phase approach as structured after the project objectives. The first is on standardized protocol development and the last is on pilot deployment. Both activities entailed interactions and close coordination among key officials and staff of DA-BAR as well as the field personnel who are the direct proponents of the identified CPAR project on : "CPAR on Integrated Rice-Rice-Vegetable+Native Chicken Farming Systems in Dingle, Iloilo." Preliminary project outputs were very encouraging as all concerned personnel were very cooperative and receptive to the intents of the project. An initial set of guidelines were crafted as well as the stock-take forms were filled up with available data from the CPAR project then uploaded via Google Docs for online and realtime updating. A complete response from the CPAR project implementation team was also received indicating support and commitment to help further enhance the project outputs. Through this initial and pilot step, BAR's M&E process specifically for CPAR is being provided with an opportunity with the right environment to enable all users to be sensitive to information and thus foster the creation and harnessing of knowledge. It is also confidently expressed that this initial step may pave the way to a more expanded and comprehensive stock-taking of data to cover all other CPAR projects and eventually lead to a unified information system that will consolidate all other types of R&D projects being funded and coordinated by BAR.